Grinding Assistance in the Transformation of Gibbsite to Corundum - Torres Sánchez, Rosa María (2002)
After gibbsite was milled for 5 min in a Cr-steel oscillating mill, corundum was obtained by heating the powder for 3 h at 800 °C. We found that iron contamination, produced by the milling process, is essential to attain the transformation at this low temperature and is located at the surface of the gibbsite particles. The knowledge of the oxidation state and location of the contaminant elements, necessary to control the solid-state reactions and/or phase transformations induced by the milling, was realized in this work by a characterization performed by chemical analysis, x-ray photoelectron spectroscopy, Mossbauer spectroscopy, and isoelectric point determination. The iron contamination amounted to about 3% (as Fe₂O₃) for the sample milled for 60 min. That the iron contamination that occurred mainly on the gibbsite amorphous surface was concluded after a comparison of the isoelectric point determination of the milled samples with that of a mechanical mixture of gibbsite and hematite. X-ray diffraction studies showed that gibbsite looses its crystallinity after the first 5 min of milling.